Designing sustained content-based lessons for secondary students - Manuel, Joel B. (2007)
This study was designed to develop materials for the implementation of the Sustained Content-Based Curriculum (CBI) in the secondary schools as the major thrust of the Basic Education Curriculum (BEC). A set of procedure was followed in this qualitative study. The materials were validated with criteria focusing on objectives, text, activities and students, format and technology and support materials and assessment. The materials were found to meet all the criteria of the evaluation instrument which showed that they met the set objectives. Said materials were also subjected to readability test with the use of online tool called Textalyzer and they were found to be generally easy for the second language learners who are fourth year high school students.